1998
DOI: 10.1177/019459989811800529
|View full text |Cite
|
Sign up to set email alerts
|

Myringoplasty in Children: Factors Influencing Surgical Outcome

Abstract: Age, size, and site of perforation, condition of the ear, status of the contralateral ear, grafting materials, and more are considered factors influencing the success rates in myringoplasties in children. The ambivalence in results is mainly due to nonhomogeneous patient groups. In an effort to compose groups as homogeneous as possible for analysis of influencing factors, a retrospective study of 51 pediatric myringoplasty cases (51 ears) was undertaken. All patients had perforations caused by simple chronic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
90
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 20 publications
15
90
1
2
Order By: Relevance
“…Thus, the patients experience only minor or moderate hearing impairment during packing, as documented by the hearing tests. The take rate of 96% is in agreement with international standards of unilateral tympanoplasty type I [8] but not in accordance with three previous studies showing that the presence of bilateral perforations adversely influence the success rate [9][10][11]. No adverse influence was noted in the two previous studies on bilateral surgery, in which the take rate was 91% in the study by Mitchell et al [4] of fat myringoplasty and 85% in the study of Katsura et al [5] of 17 patients operated by underlay techniques.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, the patients experience only minor or moderate hearing impairment during packing, as documented by the hearing tests. The take rate of 96% is in agreement with international standards of unilateral tympanoplasty type I [8] but not in accordance with three previous studies showing that the presence of bilateral perforations adversely influence the success rate [9][10][11]. No adverse influence was noted in the two previous studies on bilateral surgery, in which the take rate was 91% in the study by Mitchell et al [4] of fat myringoplasty and 85% in the study of Katsura et al [5] of 17 patients operated by underlay techniques.…”
Section: Discussionsupporting
confidence: 51%
“…Of those with taken graft 64 out of 66 has perfect graft at follow-up. These results are in line with data reported in the literature [4,[14][15][16]. Two cases of 66 successful case (approximately 3%) experienced secondary complications in the form of blunting of the anterior angle and tympanic membrane retraction.…”
Section: Discussionsupporting
confidence: 91%
“…The site of perforation did not statistically affect the outcome in our series as has been previously reported by others [4,9,15,16]. They suggested that, surgical outcome of pediatric tympanoplasty was not affected by the site or the size of perforation.…”
Section: Site Of Perforationsupporting
confidence: 84%
See 1 more Smart Citation
“…Pediatric age group was kept out of this study because this age group is still considered to have high failure rate because of possibilities of eustachian tube dysfunction, middle ear effusion and patient management problems [9][10][11]. Elderly population was excluded from the study because of many associated medical problems like diabetes mellitus, hypertension, presbyacusis and sensory neural hearing loss.…”
Section: Discussionmentioning
confidence: 99%